(untitled) (Research, Society and Development, 2020)
Objective: to identify in the scientific literature how phytotherapycan pe applied to breastfeeding. Method: this is an integrative literature review, with a survey carried out between November 2018 and december 2019 in the following databases, US National Library of Medicine, Latin American and Caribbean Center on Health Sciences Information, Scopus and US National Institutesof Health, using the following descriptors "Phytotherapy" and "Breastfeeding" and "Nursing", in which 14 articles were selected in Portuguese, English and Spanish, from 2015 to 2019. Results: observed the use of phytotherapy for the production of breast milk, but further studies are needed to show more security for the mother-baby binomial, since a recurring adverse effect occurs with gastrointestinal disorders, in addition to the intoxication resulting from the use. The fenugreek plant is the most used as galactagogues. Conclusion: phytotherapy as a galactagogue resource used by lactating women has several infl uences, are not always used safely. Nursing is faced with the need for more studies that move towards ensuring use and training.